Exosome circ-CBLB promotes M1 macrophage polarization in rheumatoid arthritis through the TLR3/TRAF3 signaling axis - Zhang, Mengyu; Wan, Lei; Zhang, Xiaojun; Wang, Siyu; Li, Feng; Yan, Dawei (Frontiers in Immunology, 2025)
BackgroundRheumatoid arthritis (RA) is a chronic autoimmune condition characterized by persistent inflammation of the joint’s synovial membrane. This inflammation leads to the degradation of joint cartilage and bone, resulting in joint dysfunction and deformity. Early symptoms of RA are often subtle, complicating timely diagnosis. Identifying potential markers for RA is therefore critical.Purpose and study designThis study aimed to explore the role of circular RNA CBLB (circ-CBLB) in RA by examining its influence on the Toll-like receptor 3/TNF receptor-associated factor 3 (TLR3/TRAF3) signaling axis and its effects on macrophage polarization through exosomes.ResultsWe found that exosomes may contribute to macrophage polarization, as shown through exosome uptake assays and flow cytometry. Clinical data reveal low expression levels of circ-CBLB in rheumatoid arthritis patients, correlating negatively with immunoinflammatory indices. Overexpression of circ-CBLB was found to inhibit M1 macrophage polarization. Further, binding between circ-CBLB and TLR3 was confirmed using RNA Immunoprecipitation, RNA pulldown, Western blot analysis, immunofluorescence, and quantitative reverse transcription polymerase chain reaction (qRT-PCR) techniques. Inhibiting circ-CBLB or TLR3 demonstrated that the effects on macrophage polarization could be counteracted by introducing inhibitors or inducers for M2 macrophage polarization, underscoring the significant role of exosomal circ-CBLB in RA.ConclusionExosomal circ-CBLB plays a crucial role in inhibiting the TLR3/TRAF3 signaling pathway, thereby reducing M1 macrophage polarization in RA patients. These findings enhance our understanding of pathophysiology of RA and offer novel insights and methods for its diagnosis and treatment.